Correction to: EPHA2 feedback activation limits the response to PDEδ inhibition in KRAS-dependent cancer cells - Chen Yue-hong; Lv Hao; Shen Ning; Wang Xiao-min; Tang Shuai; Xiong Bing; Ding Jian; Geng Mei-yu; Huang Min (Acta Pharmacologica Sinica, 2024)
The authors are very sorry for two inadvertent mistakes in the figures: the images of immunoblot showing PDEδ expression and the corresponding GAPDH loading control in H1792 and H441 cells in Fig. 2a were provided incorrectly. These errors were made due to our carelessness during the stage of figure preparation.